ASCILITE’s First Virtual Conference. Proceedings ASCILITE 2020 in Armidale 2020
DOI: 10.14742/ascilite2020.0147
|View full text |Cite
|
Sign up to set email alerts
|

Creating a digital learning ecosystem to facilitate authentic place-based learning and international collaboration – a coastal case study

Abstract: Authentic, place-based experiential learning is essential for students of ecology, whilst an understanding of broader human impacts is necessary for effective conservation efforts. Creating future environmental leaders requires fostering such understanding whilst building transferable skills in collaboration, communication and cultural competence. Mobile technologies and collaborative digital tools can connect students across broad geographic locations, allowing them to share experiences and build a common und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Within the context of an existing project in development that seeks to develop a mobile learning system for collaborative field-based learning across international institutional contexts (Bone et al, 2020), I describe below just one of these critical success factors defining several subfactors and assessing their feasibility in context.…”
Section: Describing a Single Critical Success Factor In Contextmentioning
confidence: 99%
“…Within the context of an existing project in development that seeks to develop a mobile learning system for collaborative field-based learning across international institutional contexts (Bone et al, 2020), I describe below just one of these critical success factors defining several subfactors and assessing their feasibility in context.…”
Section: Describing a Single Critical Success Factor In Contextmentioning
confidence: 99%
“…Our review criteria only identified two studies in ecology disciplines, both of which utilised an existing enterprise application for species identification (Pfeiffer et al 2009;Thomas and Fellowes 2017). There remains ample opportunity to develop collaborative mobile learning systems that use custom-built applications for field data collection and are integrated with the learning management systems, such as those in development in collaborative international projects (Bone et al 2020). We strongly encourage the exploration of the potential for mobile learning in these contexts, and the publication of other projects that have incorporated mobile tools in ecological and environmental sciences curricula.…”
mentioning
confidence: 99%